THE RELATIONSHIP BETWEEN STUDENTS’ ATTITUDE AND LEARNING MOTIVATION TOWARD THE STUDENTS’ ENGLISH ACHIEVEMENT AT THE FIRST GRADE IN SMAN 3 TOLITOLI - Fajar Yuniawati (Universitas Madako Tolitoli, 2020)
The aims of this research is to find out the significant correlation between the students’ attitude toward the students English achievement, to find out the significant correlation between learning motivation toward the students English achievement, and to find out the significant simultaneously between students’ attitude and learning motivation toward the students English achievement at the first grade in SMAN 3 Tolitoli. This research use quantitative analysis, the population of this research is the first grade of SMAN 3 Tolitoli and the sample of this research are 33 students. The researcher used questionnaire as the main technique of collecting the data, the result of this research showed that there was significant correlation between students’ attitude toward the students English achievement, it is proved Tcount2,1113>Ttable 2,045. The second, there was no significant correlation between learning motivation toward the students English achievement, it is proved Tcont0,3234<T table 2,045, the third there was no significant simultaneously between students’ attitude and learning motivation toward the students English achievement it is proved sig f change 0,136>0,05. The conclusion from this research there was no significant simultaneously between students’ attitude and learning motivation toward the students English achievement.Keyword: Attitude, motivation, achievement